Development, religious affiliation, and social context: Substance use disorders in Puerto Rican transitional age youth - Saunders, David; Sussman, Tamara; Corbeil, Thomas; Canino, Glorisa; Bird, Hector; Alegria, Margarita; Duarte, Cristiane S. (Frontiers in Psychiatry, 2023)
Introduction: Transitional age youth (i.e., ages 16-24; TAY) use higher levels of substances than any age group in the United States. Understanding what factors increase substance use during TAY could suggest novel targets for prevention/intervention. Studies suggest that religious affiliation is inversely associated with substance use disorders (SUDs). However, the association of religious affiliation and SUD, including the role of gender and social context, has not been studied in TAY of Puerto Rican ethnicity. Methods: Using data from N=2,004 TAY of Puerto Rican ethnicity across two social contexts - Puerto Rico (PR) and the South Bronx, NY (SBx) - we tested the association of religious identity (Catholic, Non-Catholic Christian, Other/Mixed, and no religious affiliation, or “None”), and four SUD outcomes (alcohol use disorder, tobacco use disorder, illicit SUD, and any SUD). Logistic regression models were used to examine the association between religious identity and SUDs, then we tested for interaction by social context and gender. Result: Half the sample identified as female; 30%, 44% and 25% were 15-20, 21-24, and 25-29 years of age, respectively; 28% of the sample received public assistance. There was a statistically significant difference between sites for public assistance (22% and 33% in SBx/PR, respectively; p<0.001); 29% of the sample endorsed None (38% and 21% in SBx/PR, respectively.) Compared to None, identifying as Catholic was associated with reduced risk of illicit SUD (OR=0.51,p=0.02), and identifying as Non-Catholic Christian with reduced risk for any SUD (OR=0.68,p=0.04). Additionally, in PR but not SBx, being Catholic or Non-Catholic Christian was protective for illicit SUD when compared to None (OR=0.13 and 0.34 respectively). We found no evidence of an interaction between religious affiliation and gender. Discussion: The percentage of PR TAY who endorse no affiliation is higher than the general PR population, reflective of increasing religious non-affiliation among TAY across cultures. Critically, TAY with no religious affiliation are twice as likely as Catholics to have illicit SUD, and 1.5 times as likely as Non-Catholic Christians to have any SUD. Endorsing no affiliation is more adverse for illicit SUD in PR than the SBx, underscoring the importance of social context.